Avaliação clínica, videolaringoscópica e vocal perceptivo-auditiva e acústica de professores disfônicos - Pereira, Eny Regina Bóia Neves [UNESP] (2014)
Professors are considered a risk group for dysphonic which are related to work conditions. Goals: Analyze the clinical, vocals and videolaryngoscopic aspects in dysphonic professors. Methodology: 90 dysphonic professors that filled out a form about voice, comorbities and work conditions, were submitted to vocal auditory perception analyses (Maximum phonation time and GRBASI scale), acoustic (MDVP program) and videolaryngoscopies. A control group formed by 90 dysphonic patients, all of them being similar in gender and age, with different professional activities from what they graduated from and the singing. Results: In both groups there were 85 women and 5 men (average age between 31 and 50 years old). In the control data most worked in domestic activities and most of the teacher taught in elementary school (42,8) and high school (37,7%). The results of the registered parameters for the professors and in the control groups were: Vocal abuse (76,7%; 37,8%), workload between 21 to 40 hours a week (72,2%; 80%), time in the job below 10 years (36%; 23%), absenteeism (23%; 0%), sinonasal symptoms 66%; 20%), gastroesophageal (44%; 22%), hoarseness(82%; 78%), hawk(70%; 62%), effort to speak 72%; 52%). The vocal analyses indicate, in both groups, decreased values of the Maximum Timing of Formation, commitments of the G parameter from the GRBASI scale (82%), decrease of f0 and elevation of the others acoustic parameters. Nodules and acid laryngitis prevailed in the professors and acid laryngitis, polyps and groove in control group. Conclusions: vocal symptoms, comorbidades and absenteeism prevailed in the teachers. The vocal perceptual and acoustic analyses were compromised in a similar manner. Nodules and acid laryngitis prevailed in the professors groups, polyps, acid laryngitis and vocal sulcus in the control